Energetic Aqueous Batteries. Issue 27 (1st June 2022) - Ju, Zhengnan; Zhao, Qin; Chao, Dongliang; Hou, Yang; Pan, Hongge; Sun, Wenping; Yuan, Zhongyong; Li, Hui; Ma, Tianyi; Su, Dawei; Jia, Baohua
Abstract: Rechargeable aqueous batteries are considered to be one of the most effective energy storage technologies to balance the cost‐efficiency, safety, and energy/power demands. The further progress of aqueous batteries with high energy density is needed to meet the ever‐increasing energy‐storage demands. This review highlights the strategies proposed so far to pursue the high energy density aqueous batteries, including the aspects of the electrolytes (from concentrated to dilute), the electrode chemistry (from inserted to converted), the cathode materials (from inorganic to organic), the anode materials (from compound to metallic), and the battery configurations (from integrated to decoupled). Critical appraisals of the emerging electrochemistry are presented for addressing the key issues in boosting the energy densities. Finally, the authors render insights into the future development of high‐energy aqueous batteries. Abstract : Aqueous batteries have become a hot research topic due to their advantages of high safety, low cost, and easy manufacturing. The pursuit of higher energy density for aqueous batteries is the key to their applications that can compete with current commercial batteries. A comprehensive overview focusing on the research progress in high energy density aqueous batteries is discussed.